2022
DOI: 10.5688/ajpe8567
|View full text |Cite
|
Sign up to set email alerts
|

The Student Engagement Effect of Team-Based Learning on Student Pharmacists

Abstract: The objective of this research was to expand the perspective of student engagement by qualitatively examining how student pharmacists experienced engagement using team-based learning (TBL) pedagogy. Methods. A qualitative case study was adopted. Data were obtained from a purposeful and convenience sampling of student pharmacists (n=14) through semi-structured interviews. Initial data analysis identified common themes, followed by oriented coding of the common themes to the focal concepts of predetermined engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…We also must consider that engaging students socially to learn mathematics is critical for improving students’ numeracy knowledge [ 13 ]. TBL is effective for introducing social conditions within a community of practice where students relate to team norms at the center of student learning [ 14 ]. Carpenter et al [ 14 ] extended student engagement for a better understanding of the subjective construal underlying engagement in TBL and we can apply their findings to numeracy development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also must consider that engaging students socially to learn mathematics is critical for improving students’ numeracy knowledge [ 13 ]. TBL is effective for introducing social conditions within a community of practice where students relate to team norms at the center of student learning [ 14 ]. Carpenter et al [ 14 ] extended student engagement for a better understanding of the subjective construal underlying engagement in TBL and we can apply their findings to numeracy development.…”
Section: Discussionmentioning
confidence: 99%
“…TBL is effective for introducing social conditions within a community of practice where students relate to team norms at the center of student learning [ 14 ]. Carpenter et al [ 14 ] extended student engagement for a better understanding of the subjective construal underlying engagement in TBL and we can apply their findings to numeracy development. Their work demonstrated the social need to cognitively relate is the students’ primary mode of engaging in TBL instruction.…”
Section: Discussionmentioning
confidence: 99%
“…TBL pedagogy employs an active learning approach that places emphasis on self-directed learning, individual and team accountability, problem solving, and communication [ 20 , 21 ]. TBL is widely used in healthcare education today [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Pharmacy students have reported that TBL assists them in achieving professional competencies like working effectively as an individual in a team and performing professional collaborative activities. 25 In addition, they stated that TBL improves their ability to think critically and communicate effectively. 11,25 RAK Medical and Health Sciences University implemented online TBL through its University Management System.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, they stated that TBL improves their ability to think critically and communicate effectively. 11,25 RAK Medical and Health Sciences University implemented online TBL through its University Management System. During the online TBL, the students take individual readiness assurance tests (IRAT) and the follow-up team readiness assurance tests (TRAT) in the Online Examination Center.…”
Section: Introductionmentioning
confidence: 99%